Annama H chondrite: mineralogy, physical properties, cosmic ray exposure, and parent body history - Kohout, Tomás̆; Hopp, Jens; Trieloff, Mario (Meteoritics & planetary science, 2017)
The fall of the Annama meteorite occurred early morning (local time) on April 19, 2014 on the Kola Peninsula (Russia). Based on mineralogy and physical properties, Annama is a typical H chondrite. It has a high Ar-Ar age of 4.4 Ga. Its cosmic ray exposure history is atypical as it is not part of the large group of H chondrites with a prominent 7-8 Ma peak in the exposure age histograms. Instead, its exposure age is within uncertainty of a smaller peak at 30 ± 4 Ma. The results from short-lived radionuclides are compatible with an atmospheric pre-entry radius of 30-40 cm. However, based on noble gas and cosmogenic radionuclide data, Annama must have been part of a larger body (radius >65 cm) for a large part of its cosmic ray exposure history. The 10Be concentration indicates a recent (3-5 Ma) breakup which may be responsible for the Annama parent body size reduction to 30-35 cm pre-entry radius.
Gesehen am 07.11.2018